Colistin Resistance among Enterobacteriaceae Isolated from Clinical Samples in Gaza Strip. (20th April 2021) - Qadi, Mohammad; Alhato, Safaa; Khayyat, Rasha; Elmanama, Abdelraouf A.
Abstract : Bacterial infections, especially drug-resistant infections, are a major global health issue. The emergence of multidrug-resistant (MDR) strains of Enterobacteriaceae and the lack of new antibiotics have worrisome prospects for all of humanity. Colistin is considered the last-line drug for MDR Gram-negative bacteria (GNB), and it is often used for treatment of respiratory infections caused by MDR-GNB. In recent years, there has been a marked increase in the incidence of colistin-resistant infections. The main objective of this study was to investigate the presence of colistin resistance among clinical GNB isolated from Gaza Strip hospitals. Clinical Enterobacteriaceae isolates (100) were obtained from microbiology laboratories of the hospitals of different geographical locations in Gaza Strip Governorate over a period of six months. Samples were cultured, and bacterial identification was performed by standard microbiological procedures. Enterobacteriaceae isolates were tested for their antimicrobial susceptibility by the disk diffusion method and the MIC method for colistin. Varying degrees of susceptibility were observed for the isolates against the tested antimicrobials even within members of the same antimicrobial class. Amikacin was the most effective drug (74%), followed by chloramphenicol (48%), fosfomycin, and gentamicin (45%). High resistance was recorded against trimethoprim (85%) and tetracycline (83%). Only 59% of the tested isolates were interpreted as susceptible, while 41% was classified as resistant. The highest resistance to colistin was found to be among the Proteus spp. (63.2%), followed by Serratia spp. (57.1%). The lowest resistance was observed among Klebsiella isolates (31.6%). Only 39.0% of meropenem-resistant Enterobacteriaceae was susceptible to colistin, while 45.8% of imipenem-resistant Enterobacteriaceae was susceptible to colistin. The overall resistance to colistin was high (41%) among tested clinical isolates. Furthermore, 89% was MDR. These limit and complicate treatment options for the infections caused by Enterobacteriaceae in Gaza Strip. This calls for immediate actions to control and monitor the use of antimicrobials in general and colistin in particular.